Human Leukemia-Associated Anti-Nuclear Reactivity - Klein, George (1974)
A brilliant, coarsely granular nuclear antigen was detected by anti-complement immunofluorescence in the nuclei of acute myeloid leukemia myeloblasts. Designated as LANA (leukemia-associated nuclear antigen), the reactivity differs from that of the Epstein-Barr-virus-determined nuclear antigen (EBNA) in immunological specificity and morphological appearance, although it is visualized by the same method. Serum from acute myeloid leukemia patients gave positive reactions in 73% of the cases. In acute lymphatic leukemia, chronic myeloid leukemia, chronic lymphatic leukemia, and Burkitt's lymphoma the sera were positive in 35, 14, 19, and 24%, respectively. Two of five polycythemia and two of eleven myeloma sera were also positive. Among 61 healthy controls, 58 were negative, whereas three showed a diffuse nuclear staining with a different pattern. Among 24 carcinoma patients, 18 were negative, whereas six gave a nuclear staining with a different, diffuse pattern. Sera from 20 patients who had recovered from infectious mononucleosis were all negative. In addition to the blasts of acute myeloid leukemia, a similar reactivity was seen with two Epstein-Barr virus DNA and EBNA-negative African lymphoma biopsies and in a short-lived tissue culture line derived from one of them. LANA could be a fetal or tissue-specific antigen, a virally determined antigen, or a specific form of anti-nuclear reactivity.